(untitled) (Bangladesh Journal of Dental Research & Education, 2014)
There had been a long standing requirement for dental students which would help them to understand the basic techniques for intraoral periapical radiographs. Intra oral periapical radiography is an adjunct to the clinical examination and provides useful information about the joint components. The periapical view shows the entire crown and root of the teeth which provides vital information to aid in the diagnosis of the most common dental diseases. This article highlights the basic principle, techniques, advantages and disadvantages of intraoral periapical radiography. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20255 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 83-87